Design of heavy-duty pavements incorporating a granular interlayer - Ahmed, Imtiaz (2020)
Pavements have been used to transport goods and people from one place to another over the years. Pavement construction technologies have been continuously evolving starting from compacted ground to brick roads and modern hot mix asphalt roads capable of speed, safety, durability and comfort. The advancing construction technologies have led to heavy-duty pavements (Inverted Pavements) in South Africa to accomodate heavy loads in warm climates. Inverted Pavements are types of pavement in which the layer arrangement is different from that of a conventional flexible pavement. In an inverted pavement, the unbound granular base layer is constructed just under the hot mix asphalt surfacing and another granular layer modified with cement is constructed underneath it. This current project involves designing inverted pavements based on laboratory testing. The project is divided into different phases which are summarised here. As a low stiffness unbound layer is constructed in a sandwich between stiffer layers, its performance becomes one of the determining factors relating to the pavement’s resistance to failure. Therefore, extensive laboratory testing has been performed in the current project to study unbound material performance under different influencing factors including moisture, fines content, number of load applications and stress conditions. The results show that the selected unbound granular material (UGM) gradations based on South African base specifications performed significantly well under these influencing factors. The resilient and permanent deformation performance of unbound granular materials is presented in detail in this thesis. The second phase of the project involved testing different inverted pavement combinations in the laboratory to establish the effect of layer thickness on performance under given loading and environmental conditions. Permanent deformation and reflective cracking were the criteria to assess the pavement performance under load. Different laboratory testing matrices were developed for permanent deformation and reflective cracking. The testing was performed at different temperatures under the same load to evaluate the pavement’s resistance to both failure criteria in a wheel tracking device. A conventional mould was used for evaluating permanent deformation while a new mould was designed and manufactured for studying crack initiation and propagation. The results showed that the different thickness combinations within an inverted pavement performed differently with some of the thickness variations affecting the performance significantly. The third phase of the project involved the prediction of permanent deformation and crack propagation in inverted pavements. Different techniques were combined to develop a methodology to predict the permanent deformation in a full-depth inverted pavement. The predicted permanent deformation values were compared with the measured ones and very close correspondance was observed. Similarly, crack initiation and propagation were also predicted by developing a mechanics-based methodology calculating the forces and hence bending in asphalt surfacing leading to calculation of tensile strains. The calculated strains were used to develop a fatigue characteristic. The methodology developed was applied to a real pavement and promising results were obtained.